Discounting earnings with stochastic discount rates - Marco Realdon (The European Journal of Finance, 2019)
This paper presents new equity valuation formulae in closed form that extend the abnormal earnings growth (AEG) valuation of Ohlson andJuettner-Nauroth (2005) to the cases of stochastic cost of capital or stochastic interest rates. Interest rates are modeled by quadraticterm structure models. Valuation can be very sensitive to the correlation between the factors driving earnings and interest rates.